The Impact of Cosumersâ Attitude on Online Video Advertising towards Product Branding - Gunawan, Lunardi (iBuss Management, 2015)
Online video advertising is becoming much more common and data shows that companiesâ demand for online video advertising is increasing rapidly. However, there is a scarcity of research done about the consumersâ perspective on online video advertising and there is still little evidence that online video advertising is beneficial for companies and the products being advertised. This research would like to find out the impact of consumersâ attitude on online video advertising towards product branding. Consumer attitude itself is divided into cognitive, affective and behavioral components. The research was done using Android One as the case study. 100 respondents from Surabaya were taken and personally asked to watch the online video advertising and fill in questionnaires. Data from the questionnaires were analyzed using multiple linear regression. Results show that consumersâ attitude on online video advertising has significant positive effect towards product branding and all three component of consumer attitude have significant positive effect towards product branding individually with affective component having the most impact. Therefore it is recommended to promote using online video advertising and create online video advertising that focus more on giving affective impact to consumers. Keywords: Consumer Attitude, Online Video Advertising, Product Branding Â